Epistemological Obstacles in Solving Equation of Straight Line Problems - G Kadarisma; R Amelia (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Epistemological obstacle is one of the learning obstacles that need enough attention in overcoming it, Epistemological obstacle is the learning barrier that occurs because of the limitations of the context possessed by the students. This study aims to analyze epistemological obstacle that occurs when students solve the problem on the topic of equation of straight line, the method in this research is qualitative descriptive involving 32 students in class 9th grade and thetest instrument used is 4 problem description of equation of straight line, Result from research most students experience epistemological obstacle in solving straight-line equations, especially in determining the equation of lines if the gradient is unknown, this is because students only know the general form formula of straight-line equations only, by knowing the obstacle epistemology that happens is expected to help the teacher to make the design didactic materialof a straight-line equation that corresponds to the epistemological obstacle that occurs.